Pengembangan Bahan Ajar Handout Untuk Pembelajaran Biologi Siswa Kelas X di SMA Negeri 1 Tegaldlimo Banyuwangi - Bima Apry Anggara; I Wayan Sukra Warpala; Ketut Srie Marhaeni Julyasih (Jurnal Pendidikan Biologi Undiksha, 2022)
This study aims to determine product design, validity and practicality of handout teaching materials. This study uses the ADDIE model (analyze, design, development, implementation, and evaluation). The trials carried out were validity tests and practicality tests by distributing questionnaires to material experts, media experts and students. The location of the trial was at SMA Negeri 1 Tegaldlimo. The results of the research are, product design produces handout teaching materials, the validity of handout teaching materials is 79.9% with appropriate criteria, and the practicality of handout teaching materials is 88.8% with very feasible criteria. Based on these results, the handout teaching materials are feasible and very practical to use in class X biology learning at SMA Negeri 1 Tegaldlimo.